Indonesian MSMES Resilience During Covid-19 Pandemics - Prima Naomi; Christharyanto, Handrix; Mayasari, Iin; Risza, Handi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Throughout the crisis in 1997-1998 and 2008-2009, the role of the MSME sector was to safeguard the national economy from turmoil, but this was not the case with the COVID-19 pandemic crisis. MSMEs have become a sector that has been heavily impacted. Therefore, the discussion on the resilience of MSMEs during disruption is important to bring valuable lessons and recommendations for the stakeholders to help MSMEs revert from the recession. This study aims to document studies that have been carried out by academics and the media on MSMEs resilience during pandemic. Some studies highlight its characteristics, others highlight the developmental perspective. Some research focuses on workers and their lead and on business processes and models. Some researchers aim at how MSMEs anticipate, foresee, and respond to disruption; while others pinpoint the intervention to increase MSMEs resilience. At the end, theoretical framework related to MSMEs resilience is drawn to conclude the findings. The resilience does not merely come from the individual and organization level. Supportive ecosystem is imperative to preserve the resilience.